2019
DOI: 10.1001/jamanetworkopen.2019.11944
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Light Flashes vs Sham Therapy During Sleep With Adjunct Cognitive Behavioral Therapy on Sleep Quality Among Adolescents

Abstract: Key PointsQuestionCan adjustment of circadian timing through light flash therapy during sleep increase total sleep time in teenagers?FindingsIn this double-blind, placebo-controlled, randomized clinical trial of 102 adolescents, light flash therapy alone was ineffective. When delivered in combination with a cognitive behavioral therapy meant to encourage an earlier bedtime, the combination of light flash therapy and cognitive behavioral therapy significantly and stably increased total sleep time by nearly 45 m… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
16
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(16 citation statements)
references
References 47 publications
0
16
0
Order By: Relevance
“…On the other hand, Danielsson et al found an overall rate of protocol failure because of “never use the light box” in 16% (19 out 57) patients with delayed sleep phase disorder in a study of 4-week CBT following either 2 weeks of BLT or the control condition; however, the impact of CBT on BLT could not be evaluated, as BLT was completed before CBT [ 39 ]. Interestingly, in a larger trial involving 102 adolescents who complained of delayed sleep, the combination of light flash therapy plus CBT resulted in a seven-fold greater increase in bedtime compliance than that observed in the group with sham plus CBT [ 40 ]. This suggests that, reciprocally, BLT might also improve adherence to prescribed sleep schedules in CBT.…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, Danielsson et al found an overall rate of protocol failure because of “never use the light box” in 16% (19 out 57) patients with delayed sleep phase disorder in a study of 4-week CBT following either 2 weeks of BLT or the control condition; however, the impact of CBT on BLT could not be evaluated, as BLT was completed before CBT [ 39 ]. Interestingly, in a larger trial involving 102 adolescents who complained of delayed sleep, the combination of light flash therapy plus CBT resulted in a seven-fold greater increase in bedtime compliance than that observed in the group with sham plus CBT [ 40 ]. This suggests that, reciprocally, BLT might also improve adherence to prescribed sleep schedules in CBT.…”
Section: Discussionmentioning
confidence: 99%
“…Consistent and earlier bedtimes among younger children lead to decreased sleep onset latency and increased sleep duration, in both longitudinal and interventional studies. 150 Several small randomized controlled trials have shown that it is possible to improve sleep routines and sleep duration in children 151 , 152 , 153 and in adolescents 139 , 154 , 155 , 156 using educational interventions, phone‐ or text‐based coaching, the provision of beds and bedding if children and adolescents lack adequate bedding. Two randomized controlled trials demonstrated that not only are such interventions associated with improved sleep hygiene but have also been associated with reductions in adiposity.…”
Section: Treatment and Outcomes: Inadequate Sleep Duration Sdb And Osamentioning
confidence: 99%
“…the contrast λ 10 compares the effect of factors A and B both at level "1" versus when they are both at level "0". For example, in a recent study, Kaplan et al (2019) considered the contrasts (−1, 1, 0, 0) and (0, 0, −1, 1).…”
Section: Contrasts Among Treatmentsmentioning
confidence: 99%